The Patkoi Nagas - Sardeshpande, S. C., 1934- (Delhi : Daya Pub. House, 1987)
On the social life and customs of the Khiamnungan and Konyak people living on both sides of the Patkoi Range in India-Burma border.
Includes index.
Bibliography: p. [195].
Keywords: Khiamnungan (Indic people) -- Social life and customs; Konyak (Indic people) -- Social life and customs